Population Structure and Phylogenetic Relationships in a Diverse Panel of Brassica rapa L. - Bird, Kevin A.; An, Hong; Gazave, Elodie; Gore, Michael A.; Pires, J. Chris; Robertson, Larry D.; Labate, Joanne A. (Frontiers in Plant Science, 2017)
The crop species Brassica rapa L. has significant economic importance around the world. However, the global distribution and complex evolutionary history of the species has made investigating its genetic population structure difficult. Crop domestication and improvement has resulted in extreme phenotypic diversity and subspecies that are used for oilseed, food for human consumption, and fodder for livestock. These subspecies include the oilseed morphotypes. oleifera (turnip rape), ssp. dichotoma (brown sarson/toria), ssp. trilocularis (yellow sarson); ssp. rapa (turnip); and Asian leafy vegetables ssp. pekinensis (Chinese cabbage), ssp. chinensis (bok choy), ssp. nipposinica (mizuna/mibuna), ssp. rapifera (rapini/broccoli rabe), ssp. narinosa (tatsoi), ssp parachinensis (choy sum), and ssp. perviridis (komatsuna). To date, studies have had insufficient sampling to determine the relationship of all morphotypes, especially oilseed morphotypes, and questions remain over the contribution of morphotype and geographic origin to population structure. We used genotyping-by-sequencing to score 18,272 single nucleotide polymorphism markers in a globally diverse panel of 333 B. rapa National Plant Germplasm System accessions that included 10 recognized subspecies. Our population genetic and phylogenetic analyses were broadly congruent and revealed five subpopulations that were largely reflective of morphotype and geography. These subpopulations were 1. European turnips/oilseed, 2. Asian turnips/oilseed, 3. yellow/brown sarson (ssp. trilocularis & ssp. dichotoma), 4. Chinese cabbage (ssp. pekinensis) and 5. bok choy, choy sum and tatsoi (ssp. chinensis, ssp. parachinensis, ssp. narinosa). Additionally, we found evidence of polyphyly and/or paraphyly, particularly for oilseed morphotypes (ssp. oleifera and ssp. dichotoma) and turnips. The results of this study have provided improved resolution to the genetic and phylogenetic relationships of subspecies within the species B. rapa. Understanding of these relationships is key to the future genetic study and improvement of this globally important crop species.